Tramadolo: profilo farmacologico, terapeutico e farmacoeconomico - Serpe, Loredana; Pradelli, Lorenzo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2004)
Tramadol is an effective central analgesic with a dual mechanism of action: antagonism on mu-opioid receptors and inhibition of serotonin and norepinephrine reuptake. In this paper a pharmacological, clinical and economical profile of its use in pain management is provided. Tramadol has proven effective in the treatment of moderate and severe pain associated with acute and chronic conditions of different ethiology, at oral or parenteral doses of about 50-100 mg every 4-6 hours. The maximal daily dose should not exceed 400 mg, less in case of liver or kidney dysfunction. Tramadol has low potential for physical or psychological dependence; the minimal likelihood of provoking typical opioid adverse events represents an advantage over other morphine-like agents. From a pharmacoeconomical point of view, tramadol prescription appears to be efficient: the comparisons conducted in the management of post-surgical pain have shown tramadol to be more convenient than the studied alternatives. Overall, tramadol appears to be a safe and effective drug for the management of pain and it is one of the most relevant week opioids to be used in the second step of the pain management latter proposed by the WHO. The recent introduction of generic tramadol permits to choose among more products and allows to obtain savings on the cost of managing acute and chronic painful conditions.